Enterotoxin and cytotoxin production by enteroinvasive Escherichia coli. - Fasano, A (1990)
It has long been suspected that besides their ability to invade enterocytes, enteroinvasive Escherichia coli (EIEC) strains have the ability to elaborate an enterotoxin. We tested 35 EIEC strains for cytotoxins and 9 (1 per serogroup) for enterotoxins. All 35 strains exhibited low levels of Vero cell cytotoxins that are immunologically and genetically distinct from Shiga-like toxin I or II of enterohemorrhagic E. coli. Sterile supernatants and cell lysates of two EIEC strains were tested in rabbit ileal loops, and both stimulated moderate fluid accumulation (circa 0.5 ml/cm) without tissue damage; secretory activity was confirmed in Ussing chambers, where these two strains and the seven others tested significantly increased short circuit current without altering tissue conductance. Curing the 140-MDa invasiveness plasmid from an EIEC strain did not diminish enterotoxin production. Culture in minimal Fe2+ medium is necessary to detect expression of the enterotoxin which is circa 68 to 80 kDa in size and is distinct from the EIEC cytotoxin.